Effect of Capital Structure and Dividend Policy on Firm Value in an Emerging Market: Evidence from Vietnam - Pham Thi Thuy Hang; Le Quang Khai; Le Vinh Phuc; Do Hong Nhan (My University, 2022)
Effect of Capital Structure and Dividend Policy on Firm Value in an Emerging Market: Evidence from Vietnam
Keywords: Capital structure